The Ethnopragmatics of Akan Advice - Agyekum, K. (Pragmatics, 2019)
This paper discusses Akan Advice under ethnopragmatics. It adopts persuasion, speech acts of directives and expressives, and Akan proverbs to discuss advice with the insight from Akan culture. The adviser expresses some feelings and emotions and directs the advisee to act and behave towards the benefits of the individual, the group or society. The paper taps data from participant observations and audio taped recordings at arbitrations, marriage and naming ceremonies. There is another data from Adi’s (1973) Akan literature book, Brako that covers pieces of advice on travelling, settlement and occupation. The Akan texts are translated into English and analysed. The analysis covers semantics, pragmatics, stylistic devices, and proverbs.
Keywords: Cultural Scripts; Akan; Ethnopragmatics; Persuasion; Directives; Expressives; Proverbs; Advice